Coordination reactions and layer exchange processes at a buried metal-organic interface - Chen, Min; Röckert, Michael; Xiao, Jie; Drescher, Hans-Joerg; Steinrück, Hans-Peter; Lytken, Ole; Gottfried, J. Michael (Journal of Physical Chemistry C, 2014)
The reactive interface between phthalocyanine (2HPc) and a Cu(111) surface was investigated with X-ray photoelectron spectroscopy (XPS) and temperature-programmed desorption/reaction (TPD/TPR). 2HPc reacts with Cu(111) to form copper(II) phthalocyanine (CuPc). For 2HPc submonolayers, the reaction starts already below 240 K. Thin 2HPc multilayers (4 monolayers) are completely converted into CuPc at elevated temperatures (500 K). To understand how molecules can react even though they are initially not in contact with the Cu surface, TPD/TPR studies with a NiPc interlayer between Cu and 2HPc were performed. These studies reveal the operation of an exchange mechanism, by which CuPc or NiPc molecules from the first layer are replaced by 2HPc molecules from higher layers. Once a 2HPc molecule comes into contact with the Cu surface, the molecule can react with the surface, forming CuPc, which can then be replaced by another unreacted 2HPc molecule. These findings have important implications for metal-organic interfaces in organic electronic devices, in which the charge carrier injection at the electrodes depends on the electronic properties of the interface. © 2014 American Chemical Society.